Breeding biology of tawes (Puntius gonionotus Bleelcer - Hoque, Muhammad Tafazzal; Ahmed, Abu Taweb Abu (Indian Journal of Fisheries, 2011)
Breeding biology of pond-reared to-oods of Puntius gonionotus Bleeker was undertaken with special reference to its induced breeding, using carp pituitary homogenate (cph), and other reproductive aspects. An attempt was made to investigate anid develop the most viable technique under controlled hatchery condition lox seed production of the species.